Synthesis and Characterization of High-Quality Ta2O5 Nanoparticles for Highly Selective SAW-Based DUV Sensor and Corona Detection Application - Kim, Sihyeok; Nawaz, Faisal; Choi, Cheol; Jeon, Il; Lee, Keekeun (Advanced Materials Technologies, 2024)
In recent times, significant progress is made in the development of solar-blind deep-ultraviolet (DUV) photodetectors (200–280 nm) due to their potential applications for military and civil purposes. In this study, the development of a novel solar-blind DUV photodetector based on tantalum pentoxide (Ta2O5) nanoparticles (NPs) utilizing Surface Acoustic Wave (SAW) sensor integrated with Interface electronics is reported for the first time. The 3-D Ta2O5 NPs surface morphology, crystallinity, and defect state level is discussed using various analytical techniques, including scanning electron microscope (SEM), X-ray diffraction (XRD), and spectrophotometer. The developed 3-D Ta2O5 NPs based photodetector exhibits high sensitivity to 254 nm DUV irradiation (5 µW cm−2), demonstrating excellent photoresponse characteristics. The performance parameters including highest sensitivity, fast response/recovery time are measured as 1621.1 ppm (mW cm−2)−1, 3.7s/19.8s, respectively. Subsequent analysis demonstrates the stability and repeatability of the photodetector, enabling its potential to real time corona discharge detection. With its inherent advantages, the current DUV photodetector utilizing Ta2O5 NPs exhibits great potential for future applications in DUV optoelectronics.
Keywords: Corona discharge detection; Corona discharges; Deep ultraviolet; Deep-ultraviolet sensor; Sensor interface; Solar blind; Surface acoustic waves; Ta2O5 nanoparticle; Ultra-violet photodetectors; Ultraviolet sensors; corona discharge detection; DUV sensors; sensor interfaces; surface acoustic waves; Ta2O5 nanoparticles